Record based analysis of indications and complications of 500 cases of lower segment cesarean sections at a tertiary care hospital - Chaurasia, Vaishali; Shrivastava, Sushruta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The drastically increasing rate of caesarean section is a topic of constant worry and analysis throughout the world. In order to understand the degree to which caesarean section may be preventable, it is important to know why caesarean section are performed. This study is aimed to find out the rate of caesarean section at our institute, various indications of the procedure and complications related to them. Methods: This study was carried out retrospectively in the department of obstetrics and gynecology at Chirayu Medical College and Hospital, Bhopal. Study period was from January 2017 to December 2017. 500 cases of lower segment cesarean section were studied including both elective and emergency caesarean sections. Statistical analysis of age, parity, period of gestation, indications of LSCS and complications was done. Results: The rate of caesarean section came out to be 47.7%, which is far above recommended. Majority of patients (81.6%) were in 21-30 years age group; while the number of primary and repeat caesarean section were comparable (40.8% and 59.2%respectively). Commonest indication was previous LSCS (31.6%) followed by fetal distress (21.6%). Surgical site infection was present in 4.6% cases whereas, post-partum hemorrhage occurred in 5.8% cases. Three patients underwent obstetric hysterectomy and two cases of maternal mortality were reported among post LSCS patients. Conclusions: Increasing rates of caesarean section has contributed to maternal morbidity along with financial burden. Individualization of the indication and careful evaluation, following standardized guidelines, practice of evidenced-based obstetrics and audits in the institution, can help us limit rate of caesarean section.